The ethnocultural film festival as media happening: French-Maghrebi film in Marseille. Issue 2 (1st June 2014) - Stewart, Michelle
This article analyses the efforts of a local film festival to bridge the cultures north and south of the Mediterranean by bringing North African film to Marseille. Marseille's distance from national broadcast culture underscores the city as an unlikely host for an integrative media event, but allows for an examination of how the small scale of the community film festival provides an important counterpoint to the national thrust of the broadcast media event. Such festivals are non-broadcast media events. They are local, face-to-face, and immediate (i.e., live in a non-broadcast sense). They constitute a form of 'slow media', several days of physical presence in the theatre, focused viewing, and shared public discussion between film-makers and audiences. As such, the ethnocultural film festival is a media happening that strives to interrupt the continuous broadcast of official media events that picture the lives of minority communities in ways that run counter to their experience and understanding of them.